2004
DOI: 10.1017/s0022112004001326
|View full text |Cite
|
Sign up to set email alerts
|

Fully resolved simulations of colliding monodisperse spheres in forced isotropic turbulence

Abstract: Fully resolved simulations of particles suspended in a sustained turbulent flow field are presented. To solve the Navier-Stokes equations a lattice-Boltzmann scheme was used. A spectral forcing scheme is applied to maintain turbulent conditions at a Taylor microscale Reynolds number of 61. The simulations contained between 2 and 10 vol % particles with a solid to fluid density ratio between 1.15 and 1.73. A lubrication force is used to account for subgrid hydrodynamic interaction between approaching particles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(101 citation statements)
references
References 65 publications
11
89
1
Order By: Relevance
“…The systematic increase in the extent of carbonation with increasing wt.% forsterite (particle concentration) demonstrates the importance of particle-particle interactions (abrasion) in exposing fresh olivine reaction surfaces and enhancing carbonation reactivity. In recent simulations of colliding monodisperse spheres in forced isotopic turbulent flow, corresponding closely to the stirred tank conditions in our experiments, Derksen et al 33 identified two distinct collision mechanisms: (i) primary collisions consisting of uncorrelated "kinetic gas"-like random contacts and (ii) highly correlated secondary collision processes, involving a repetitive "chattering" motion on a short time scale, due to short-range hydrodynamic effects (lubricating forces). Elementary geometric considerations deliver a length scale (L) dependence on weight % solids, W, proportional to W -1/3 .…”
Section: Controlled Particle Abrasion: Enhancing Passivating Layer Exsupporting
confidence: 61%
“…The systematic increase in the extent of carbonation with increasing wt.% forsterite (particle concentration) demonstrates the importance of particle-particle interactions (abrasion) in exposing fresh olivine reaction surfaces and enhancing carbonation reactivity. In recent simulations of colliding monodisperse spheres in forced isotopic turbulent flow, corresponding closely to the stirred tank conditions in our experiments, Derksen et al 33 identified two distinct collision mechanisms: (i) primary collisions consisting of uncorrelated "kinetic gas"-like random contacts and (ii) highly correlated secondary collision processes, involving a repetitive "chattering" motion on a short time scale, due to short-range hydrodynamic effects (lubricating forces). Elementary geometric considerations deliver a length scale (L) dependence on weight % solids, W, proportional to W -1/3 .…”
Section: Controlled Particle Abrasion: Enhancing Passivating Layer Exsupporting
confidence: 61%
“…Direct numerical simulations of particle-laden turbulent flow with no-penetration and no-slip boundary conditions imposed at the surface of each particle are now feasible for single and even multiparticle systems. [2][3][4] With increasing computational power, using these DNS the boundary layer around each particle can be resolved. We denote these simulations as "true" DNS.…”
Section: ͑4͒mentioning
confidence: 99%
“…Two important unclosed terms are the interphase transfer of turbulent kinetic energy, and the dissipation rate of turbulent kinetic energy in the fluid phase. This paper describes a mathematical constraint that models for these terms must obey, so that they can be meaningfully compared with emerging high-fidelity direct numerical simulations [2][3][4] and experiments. 5 For particle-laden flows with non-negligible mass loading, the interphase transfer of momentum must be accounted for, and it manifests itself as the mean interphase momentum transfer term in the averaged equations of the two-fluid theory.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the particle volume fraction is high, additional models are required to account for short-range hydrodynamic solid-solid interactions (lubrication forces) and solid-solid contacts. Otherwise, the realism of the simulation may be compromised by a poor description of these interactions-for instance, by underpredicting lubrication-enhanced clustering of inertial particles, as observed for homogeneous isotropic * p.simoescosta@tudelft.nl turbulent flows [3]. The challenge is to find a model able to reproduce short-range particle-particle and particle-wall interactions with the required realism and with little effect on the computational efficiency of the overall numerical algorithm.…”
Section: Introductionmentioning
confidence: 99%